Case report: The tale of an extruding inflatable penile prosthesis cylinder into the scrotum - Taylor L. Lan; Jill S. Patel; Joseph Y. Clark (Urology Case Reports, 2025)
Cylinder extrusion through a corporotomy is a rarely reported complication of inflatable penile prosthesis. While medical comorbidities such as diabetes mellitus, cardiovascular disease, and tobacco use could increase the risk of postoperative complications, technical factors such as improper closure of the corporotomy incision or incorrect sizing of the cylinder could also increase the risk of extrusion. This case report highlights the presentation of cylinder extrusion into the scrotum after a virgin implant and the surgical management of repositioning the extruded cylinder and repairing the open corporotomy.